PENGALAMAN MAHASISWA DENGAN PENYAKIT KRONIK DALAM BELAJAR DI UNIVERSITAS ESA UNGGUL - Dewi, Ratna (Indonesian Journal of Nursing Health Science, 2016)
AbstractChronicdiseaseis a disease thatrequiresa long time, does not occursuddenlyorspontaneous, andusually can not becuredcompletely.Thisqualitative studyconducted toexplore theexperiencesof studentswithchronicdiseasesin learningthe number of4participants. Research purposesto gaina deep understanding ofthe experienceof studentswithchronicillnessesin thestudy. There are fourthemes thatobtainedin this study are1) a changeof lifedue tochronicdisease, 2) supportobtained, 3) barriers to learning, 4) expectationsforstudents. Suggestto thestudents formeda grouporclubforpeople withchronicdiseasewheremutualsupportand mutualcooperationin the process ofhealing.Â Keywords: experience, chronicillness, students, learning